Development and Evaluation of A Multifunctional Antiaging and Skin-Brightening Cosmeceutical Hydrogel Containing Niacinamide, Sodium Ascorbyl Phosphate, Hyaluronic Acid, and Herbal Bioactive Extracts - Jadhao, Sachinkumar; Jadhao, Saylee (Journal of Pharmacy Practice and Community Medicine, 2026)
Background Skin aging and hyperpigmentation are primarily driven by oxidative stress, collagen degradation, ultraviolet exposure, and environmental factors, necessitating multifunctional cosmeceutical formulations with synergistic mechanisms of action. Objectives To develop and optimize a Carbopol® 940-based multifunctional cosmeceutical hydrogel containing niacinamide, Sodium Ascorbyl Phosphate (SAP), hyaluronic acid,Aloe vera, andCamellia sinensis extracts for antiaging and skin-brightening applications. Materials and Methods Three hydrogel Formulations (F1-F3) with varying Carbopol® 940 concentrations (0.75-1.25% wt/wt) were prepared using controlled hydration and neutralization techniques. Formulations were evaluated for physicochemical characteristics, pH, viscosity (Brookfield DV-II+, spindle 64, 10 r.p.m.), spreadability, rheological behavior,in vitro antioxidant activity (DPPH assay), accelerated stability (40°C/75% RH for 90 days), and primary skin irritation (n = 6 healthy volunteers). Statistical analysis was performed using one-way ANOVA followed by Tukey’s post hoc test (p < 0.05). Results The optimized formulation (F2, 1.0% Carbopol®) exhibited pH 5.9 ±0.1, viscosity 4,850 ± 120 cP, and spreadability 6.8 ± 0.2 g cm/s, indicating optimal topical rheology. F2 demonstrated significant antioxidant activity (78.4 ± 1.6% DPPH inhibition), comparable to ascorbic acid, 94.2 ± 0.8% and significantly higher than placebo gel (8.3 ± 1.2%) (p < 0.001). Accelerated stability studies showed no significant changes in pH, viscosity, or spreadability over 90 days (p > 0.05). The Primary Irritation Index was 0.00, confirming dermatologic safety. Conclusion The optimized multifunctional hydrogel (F2) demonstrated excellent stability, safety, antioxidant activity, and optimal rheological performance. The synergistic combination of niacinamide, SAP, hyaluronic acid, and herbal antioxidants provides a promising cosmeceutical platform for antiaging and skin-brightening applications pending clinical validation.
Keywords: Cosmeceutical; Hydrogel; Antiaging; Skin Brightening; Niacinamide; Sodium Ascorbyl Phosphate; Hyaluronic Acid; Antioxidant; Topical Delivery; Stability Study